In vitro pro-inflammatory enzyme inhibition and anti-oxidant potential of selected Sri Lankan medicinal plants - Hettiarachchige Dona Sachindra Melshandi Perera; Jayanetti Koralalage Ramani Radhika Samarasekera; Shiroma Mangalika Handunnetti; Ovitigala Vithanage Don Sisira Jagathpriya Weerasena; Hasitha Dhananjaya Weeratunga; Almas Jabeen; Muhammad Iqbal Choudhary (BMC, 2018)
Abstract Background The extracts of the ten selected Sri Lankan medicinal plants have been traditionally used in the treatment of inflammatory mediated diseases. The extracts were investigated for anti-inflammatory and anti-oxidant potential in vitro to identify bio-active extracts for further chemical characterization. Methods In vitro anti-inflammatory activities of total ethanol extracts were investigated measuring the inhibitory activities of four pro-inflammatory enzymes, arachidonate-5- lipoxygenase (A5-LOX), hyaluronidase (HYL), xanthine oxidase (XO) and inducible nitric oxide (iNO) synthase. Cytotoxicity of extracts were determined by MTT assay. Oxidative burst inhibition (OBI) on human whole blood (WB) and isolated polymorphoneutrophils (PMNs) was carried out for a selected bio-active extract. Anti- oxidant activities of the extracts were determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging, ferric reducing antioxidant power (FRAP), ferrous ion chelation (FIC) and oxygen radical absorbance capacity (ORAC) assays. Total polyphenol and total Flavonoid contents of the extracts were also determined. The most active plant extract was analysed using Gas chromatography-Mass spectrometry (GC-MS) and High Performance Liquid Chromatography (HPLC). Results The ethanol bark extract of Flacourtia indica showed the highest A5-LOX (IC50: 22.75 ± 1.94 g/mL), XO (70.46 ± 0.18%; 250 μg/mL) and iNOs inhibitory activities on LPS- activated raw 264.7 macrophage cells (38.07 ± 0.93%; 500 μg/mL) with promising OBI both on WB (IC50: 47.64 2.32 μg/mL) and PMNs (IC50: 5.02 0.38 μg/mL). The highest HYL inhibitory activity was showed by the leaf extracts of Barathranthus nodiflorus (42.31 ± 2.00%; 500 μg/mL) and Diospyros ebenum (41.60 ± 1.18%; 500 μg/mL). The bark and leaf extracts of Callophyllum innophyllum (IC50: 6.99 ± 0.02 μg/mL) and Symplocus cochinchinesis (IC50: 9.85 ± 0.28 μg/mL) showed promising DPPH free radical scavenging activities. The GC-MS analysis of ethanol bark extract of F. indica showed the presence of two major bio-active compounds linoleic acid ethyl ester and hexadecanoic acid, ethyl ester (> 2% peak area). The HPLC analysis showed the presence polyphenolic compounds. Conclusion The ethanol bark extract of F. indica can be identified as a potential candidate for the development of anti-inflammatory agents, which deserves further investigations. The bio-active plant extracts may be effectively used in the applications of cosmetic and health care industry.